Pengaruh Perceived Gender equity terhadap Work Engagement pada Manager Bank X Kota Bandung - Muhammad Dzaky Anwar Muhtadin; Hendro Prakoso (Bandung Conference Series: Psychology Science, 2022)
Abstract. The research on perceived gender equity in bank X manager in Bandung was conducted because gender equality in the company environment became important for employees, especially in service companies including banks. The research method used is causality with the number of participants being 30 managers of bank X Bandung city. perceived gender equity is measured by the PGE scale by Sharma Radha. The finding show that 83.3% of managers have a high perceived gender equity, 80% of manager have a high work engagement and perceived gender equity have impact on work engagement by 53,9% Abstrak. Penelitian perceived gender equity pada manager bank X kota bandung dilakukan karena kesetaraan gender di lingkungan perusahaan menjadi penting untuk karyawan terutama pada perusahaan jasa termasuk bank. metode penelitian yang digunakan yaitu kausalitas dengan jumlah partisipan 30 manager bank X kota bandung. perceived gender equity diukur dengan PGE scale by Sharma Radha. hasil menunjukan bahwa 83,3% manager memiliki perceived gender equity yang tinggi, 80% manager memiliki work engagement yang tinggi dan perceived gender equity berpengaruh besar pada work engagement sebesar 53,9%